2021
DOI: 10.1017/s1049023x21001138
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Emergency Medical Service Missions in Out-of-Hospital Cardiac Arrest and Death Cases in the Periods of Before and After the COVID-19 Pandemic

Abstract: Background: Some studies in countries affected by the coronavirus disease of 2019 (COVID-19) pandemic have shown that the missions of Emergency Medical Service (EMS) have changed during the COVID-19 pandemic, and the rate of death and out-of-hospital cardiac arrest (OHCA) has been increased due to the direct and indirect effects of COVID-19. Objective: The aim of this study was to determine the effect of the COVID-19 pandemic on the process of EMS missions, death, and OHCA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…7 Similar studies from Italy, Iran, Finland and the USA on the influence of the SARS-CoV-2 pandemic on emergency medical services confirmed our described decline in total mission numbers, with rates from 5.7% to 23%. 5,6,8,9 In accordance with our results, another German study that investigated the area of Bavaria found the most substantial decrease of mission numbers during the first lockdown period. 10 The reasons for the drop in mission numbers are multifaceted: reaching from a change in lifestyle habits that led to a lowered risk of accidents, to the avoidance of reaching for health services because of the fear of facing an infectious disease or getting infected in the emergency department or hospitals, and to worry and ambitions not to overload the health system.…”
Section: Mission Number Dropsupporting
confidence: 91%
See 1 more Smart Citation
“…7 Similar studies from Italy, Iran, Finland and the USA on the influence of the SARS-CoV-2 pandemic on emergency medical services confirmed our described decline in total mission numbers, with rates from 5.7% to 23%. 5,6,8,9 In accordance with our results, another German study that investigated the area of Bavaria found the most substantial decrease of mission numbers during the first lockdown period. 10 The reasons for the drop in mission numbers are multifaceted: reaching from a change in lifestyle habits that led to a lowered risk of accidents, to the avoidance of reaching for health services because of the fear of facing an infectious disease or getting infected in the emergency department or hospitals, and to worry and ambitions not to overload the health system.…”
Section: Mission Number Dropsupporting
confidence: 91%
“…[1][2][3][4] During the pandemic spread of COVID-19, the utilization of prehospital emergency health services (PHEMS) decreased substantially during the lockdown periods all over the world. [5][6][7][8][9][10] PHEMS are essential to the functionality of health systems. The challenging conditions of the COVID-19 pandemic, including special requirements for personal protective equipment (PPE) and patient transport, have put PHEMS under immense pressure to adapt.…”
Section: Introductionmentioning
confidence: 99%
“… Structural/ Systemic 73 Hasani-Sharamin et. al 85 Characteristics of Emergency Medical Service Missions in Out-of-Hospital Cardiac Arrest and Death Cases in the Periods of Before and After the COVID-19 Pandemic Cross-sectional Mission data Tehran, IR ● The number of OOHCAs in 2019 was greater than that of 2018 or 2020. ● Respiratory distress and infection were more common in 2020 than 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Up to a quarter of the urban EMS missions are related to OHCA, 18 and the achievement of ROSC represents the first step in the care process for these patients. Moreover, ROSC could be considered a quality indicator for the EMS taking into account both organizational and technical aspects of the delivered resuscitation.…”
Section: Discussionmentioning
confidence: 99%